3D photogrammetry quantifies growth and external erosion of individual coral colonies and skeletons. Issue 1 (December 2017) - Ferrari, Renata; Figueira, Will; Pratchett, Morgan; Boube, Tatiana; Adam, Arne; Kobelkowsky-Vidrio, Tania; Doo, Steve; Atwood, Trisha; Byrne, Maria
Abstract Growth and contraction of ecosystem engineers, such as trees, influence ecosystem structure and function. On coral reefs, methods to measure small changes in the structure of microhabitats, driven by growth of coral colonies and contraction of skeletons, are extremely limited. We used 3D reconstructions to quantify changes in the external structure of coral colonies of tabularAcropora spp., the dominant habitat-forming corals in shallow exposed reefs across the Pacific. The volume and surface area of live colonies increased by 21% and 22%, respectively, in 12 months, corresponding to a mean annual linear extension of 5.62 cm yr−1 (±1.81 SE). The volume and surface area of dead skeletons decreased by 52% and 47%, respectively, corresponding to a mean decline in linear extension of −29.56 cm yr−1 (±7.08 SE), which accounted for both erosion and fragmentation of dead colonies. This is the first study to use 3D photogrammetry to assess fine-scale structural changes of entire individual coloniesin situ, quantifying coral growth and contraction. The high-resolution of the technique allows for detection of changes on reef structure faster than other non-intrusive approaches. These results improve our capacity to measure the drivers underpinning ecosystem biodiversity, status and trajectory.